2014
DOI: 10.3892/or.2014.2966
|View full text |Cite
|
Sign up to set email alerts
|

Latexin exhibits tumor suppressor potential in hepatocellular carcinoma

Abstract: Abstract. Hepatocellular carcinoma (HCC) is the most common primary cancer of the liver and latexin is downregulated in several types of human cancer. However, latexin expression in HCC remains unknown. mRNA expression of latexin in HCC samples and HCC-derived cell lines was detected by semi-quantitative PCR and real-time PCR, while protein expression was assessed by immunohistochemistry. The role of latexin in the regulation of the proliferation of HCC-derived cells was investigated both in vitro and in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
(31 reference statements)
1
16
0
Order By: Relevance
“…We and others have shown that Lxn is downregulated in leukemia, lymphoma, and several other cancers (Li et al., 2011, Liu et al., 2012, Mitsunaga et al., 2012, Abd Elmageed et al., 2013, Muthusamy et al., 2013, Ni et al., 2014). Since young Lxn −/− mice did not show any obvious sign of hematological malignancy, we asked whether aging could promote tumor development in Lxn −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that Lxn is downregulated in leukemia, lymphoma, and several other cancers (Li et al., 2011, Liu et al., 2012, Mitsunaga et al., 2012, Abd Elmageed et al., 2013, Muthusamy et al., 2013, Ni et al., 2014). Since young Lxn −/− mice did not show any obvious sign of hematological malignancy, we asked whether aging could promote tumor development in Lxn −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“… 3 It is downregulated in several types of solid and liquid tumors, and overexpression of Lxn inhibits tumor cell growth. 4 , 5 , 6 , 7 , 8 In lymphoma, the tumor suppressor function of Lxn is mediated through Bcl-2-induced apoptosis. 5 Moreover, Lxn was reported to be a TNF-responsive gene in human papillovirus-infected keratinocytes, suggesting that it may contribute to TNF-induced suppression of cervical cancer.…”
mentioning
confidence: 99%
“…LXN has homology to two other proteins/genes, tazarotene-induced gene 1 (TIG1) and cystatin C, both of which have been reported to be tumor suppressors (36,37). LXN expression has been suggested to be a tumor suppressor itself as it has been shown to inhibit tumor cell growth in gastric cancer (14), leukemia (15), melanoma (16), PCa (38), hepatocellular carcinoma (39) and breast cancer (40). In addition to being a potential tumor suppressor, LXN negatively regulates hematopoietic stem cell self-renewal in mice, resulting in an inverse relationship between LXN expression and HSC population size (17,18,41).…”
Section: Discussionmentioning
confidence: 99%